2006
DOI: 10.1039/b604626f
|View full text |Cite
|
Sign up to set email alerts
|

Radical reactions of [60]fullerene with β-enamino carbonyl compounds mediated by manganese(iii) acetate

Abstract: Manganese(III) acetate dihydrate-mediated reactions of [60]fullerene with beta-enamino carbonyl compounds afforded [60]fullerene-fused pyrroline derivatives, of which the nitrogen atom is directly connected to the fullerene cage. A possible reaction mechanism is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(27 citation statements)
references
References 31 publications
0
27
0
Order By: Relevance
“…However, since MnA C H T U N G T R E N N U N G (OAc) 3 is poorly soluble in organic solvents, harsh reaction conditions together with a tedious separation procedure are normally required. [88] In order to establish efficient and milder reaction conditions, Wang and co-workers investigated novel manganeseA C H T U N G T R E N N U N G (III) acetate dihydrate [Mn-A C H T U N G T R E N N U N G (OAc) 3 ·2 H 2 O]-mediated intermolecular radical additions of 1,3-cyclohexanediones to in situ generated imines under solvent-free conditions, promoted by the ball milling technique. In this study, a variety of solid aromatic aldehydes 13 were reacted in a vibration ball mill (30 Hz) with solid 4-methylaniline (85) affording quantitatively the corresponding imines after 1 h. These in situ generated imines were then directly reacted with 1,3-cyclohexanediones in the presence of MnA C H T U N G T R E N N U N G (OAc) 3 ·2 H 2 O using a ball mill (Scheme 27).…”
Section: Radical Additions To Imines Mediated By Mn(iii)mentioning
confidence: 97%
“…However, since MnA C H T U N G T R E N N U N G (OAc) 3 is poorly soluble in organic solvents, harsh reaction conditions together with a tedious separation procedure are normally required. [88] In order to establish efficient and milder reaction conditions, Wang and co-workers investigated novel manganeseA C H T U N G T R E N N U N G (III) acetate dihydrate [Mn-A C H T U N G T R E N N U N G (OAc) 3 ·2 H 2 O]-mediated intermolecular radical additions of 1,3-cyclohexanediones to in situ generated imines under solvent-free conditions, promoted by the ball milling technique. In this study, a variety of solid aromatic aldehydes 13 were reacted in a vibration ball mill (30 Hz) with solid 4-methylaniline (85) affording quantitatively the corresponding imines after 1 h. These in situ generated imines were then directly reacted with 1,3-cyclohexanediones in the presence of MnA C H T U N G T R E N N U N G (OAc) 3 ·2 H 2 O using a ball mill (Scheme 27).…”
Section: Radical Additions To Imines Mediated By Mn(iii)mentioning
confidence: 97%
“…Thus, Mn(OAc) 3 behaves as a Lewis acid as well as a radical initiator, and alters the regioselectivity. 27 Recently, they found that in the Mn(OAc) 3mediated reaction with 1-(pyridin-2-yl)-enones, replacement of 1,3-cyclohexanediones with their b-enamino carbonyl compounds afforded dihydrobenzofuran derivatives, instead of the expected 2-acyl-3-aryl-indole derivatives (Scheme 8). 28 The addition of a base such as N,N-dimethylaminopyridine (DMAP) improved the product yields, and N-unsubstituted b-enamino carbonyl compounds performed better than their N-substituted counterparts.…”
Section: Fecl 3 -Promoted Oxidative Homocoupling Of Phenolsmentioning
confidence: 99%
“…[60]Fullerenolactones (R = H, Me, Ph) were prepared in 18-41% yields by regioselective Mn(OAc) 3 mediated oxidative cyclocondensation of C-60 with carboxylic acids, carboxylic anhydrides, or malonic acids in the presence of 4-(dimethylamino)pyridine. In a recent example, radical reactions of [60]fullerene with -enamino carbonyl compounds mediated by Mn(OAc) 3 were reported [117]. In a recent example, radical reactions of [60]fullerene with -enamino carbonyl compounds mediated by Mn(OAc) 3 were reported [117].…”
Section: Manganese(iii) Acetate Mediated Reactions With Fullerenementioning
confidence: 99%